Experiences on Role Transition Among Nurse Prescribers - Suominen, Jonna; Salminen, Leena; Renholm, Marja; Sulosaari, Virpi; Virtanen, Heli (Wiley, 2025)
Aim: The aim was to describe the experiences of nurse prescribers on role transition during nurse prescriber education and working in a new role.
Background: Nurse prescribing has increased globally, bringing a new importance for nursing. Transition into a new nursing role can be motivating, satisfying, and empowering. However, it can also be stressful and complex. It is important to know how the role transition from a nurse to a nurse prescriber could already be facilitated during studies and the first working years in a new role. As little work has been conducted on this topic, there is a gap in this research area.
Methods: This phenomenological study was implemented with 14 Finnish nurse prescribers using semi-structured individual interviews. The data were analyzed with inductive content analysis.
Findings: Altogether, this study identified four main categories for experiences on role transition. These main categories are in role transition during nurse prescribing education (1) learning decision-making; (2) meaningfulness of studies during education and at the beginning of nurse prescriber role at work; (3) development of expertise; and (4) significant change in work.
Discussion: The meaningfulness of the learning and learning decision-making are important in role transition during nurse prescribing education. There is a significant development of expertise and change in work procedures during the transition from a nurse to a nurse prescriber.
Conclusions and implications for nursing: Nurse prescriber education has a key role in the transition experience from registered nurse to nurse prescriber. It is also possible that healthcare units do not utilize nurse prescribers effectively.